Praise as Pathway: Caregiver Language and Identity Construction in Pediatric Cancer Narratives - Isha Jayakumar; Hannah Taylor (Qualitative Health Research, 2026)
This qualitative interpretive study examines how praise functions in pediatric cancer narratives, focusing on two caregiver-authored blogs, Dominic’s Journey with AML and Superman Sam. The analysis identifies a longitudinal progression in which praise evolves from process-focused coping language into heroic, communal, and elegiac identity framing across treatment, crisis, and loss. These findings extend developmental and clinical work on praise, mindset, and metaphor into the underexplored domain of pediatric recovery narratives and suggest that balanced, process-centered, emotionally honest praise may better preserve space for ambivalence, fear, and ordinary childness, offering clinicians and caregivers a more flexible framework for supporting families through serious illness.